Publication rate and factors associated with the publication of papers submitted to the National Scientific Congresses held by the Peruvian Medical Student Scientific Society between 2010 and 2014 - Christian Aquino-Canchari; Karla Guillen-Macedo; Yonatan Gómez-Mamani; Juan Jhonnel Alarco (Revista de la Facultad de Medicina, 2021)
Introduction: The National Scientific Congress (NSC) is an annual event held in Peru in which medical students from all over the country present their research work.